Contesting Nordicness From Scandinavianism to the Nordic Brand - Marjanen, Jani; Strang, Johan; Hilson, Mary (Helsinki Yearbook of Intellectual History, 2021)
What makes the Nordic countries Nordic? The terms 'Nordic' and 'Scandinavian' are increasingly used in wide range of political and cultural contexts. Historically they have been associated with political projects and institutions, while also functioning as categories of analysis in academic research. Often associated with positive meanings, the term 'Nordic' has also become a resource for commercial and cultural branding.